Walkability Pada Jalur Pergantian Antarmoda Pada Kawasan Dermaga Kota Palembang - An Nurrakis; Dyah Titisari Widyastuti (UNIVERSITAS INDO GLOBAL MANDIRI, 2020)
ABSTRACTMusi river which divides the city of Palembang becomes a potential for water moda tranportation. there are four piers in the pier of city palembang. Bekang pier, Point pier, Ampera pier, Pasar 16 pier. The existence of the four piers is a generator for land transportation moda that move around the pier. For people who use land and water transportation, they move on foot, giving rise to pedestrian paths that connect land and water transit points. However, this area is not supported by good pedestrian paths and encourages intermodal users to prefer using motorized vehicles rather than walking in daily activities. To increase walking activities, it needs to be supported by a pleasant, comfortable track and a good pedestrian path. The purpose of this study is to find the level of walkability, and develop strategies to increase the level of walkability that is appropriate in the dock area of Palembang. Walkability level assessment consists of 7 (seven) variables, Accessible variables, Connected variables, Legible variables, Comfortable variables, Safe variables, Secure variables and Pleasant variables. The results show that the level of walkability in the Palembang City pier area is at a very bad level (1.4 on a scale of 5), with safety from pedestrian crime as the most influential component of walkability.Keywords : walkability, intermodal change point, city transportationABSTRAKSungai musi yang membelah Kota Palembang menjadi potensi bagi moda transportasi air. Terdapat empat titik dermaga pada kawasan Dermaga Kota Palembang, Dermaga Bekang, Dermaga Point, Dermaga Ampera, Dermaga Pasar 16. Keberadaan empat dermaga tersebut menjadi generator bagi moda transportasi darat yang bergerak di sekitar dermaga. Bagi masyarakat pengguna trnasportasi antarmoda darat dan air melakukan perpindahan dengan berjalan kaki sehingga menimbulkan jalur-jalur pejalan kaki yang menghubungkan titik transit antarmoda darat dan air. Namun, kawasan ini tidak didukung oleh jalur pejalan kaki yang baik dan mendorong pengguna antarmoda lebih memilih menggunakan kendaraan bermotor daripada berjalan kaki dalam aktivitas sehari-hari. Untuk meningkatkan aktivitas berjalan, perlu ditunjang dengan suasana jalur yang menyenangkan, nyaman serta jalur pejalan kaki yang baik. Tujuan dari penelitian ini adalah menemukan tingkat walkability, dan menyusun strategi untuk meningkatkan level walkability yang sesuai pada kawasan dermaga kota palembang. Penilaian tingkat walkability terdiri dari 7 (tujuh) variable yaitu, kemudahan akses, keterhubungan, keterbacaan, kenyamanan, keamanan dari lalulintas, keamanan dari kriminal, dan menyenangkan. Hasil menunjukkan bahwa tingkat walkability di kawasan dermaga Kota Palembang berada pada level sangat buruk (1,4 pada skala 5), dengan keamanan dari tindakan kriminal jalur pejalan kaki sebagai komponen walkability yang paling berpengaruh.Kata kunci : walkability, titik-titik pergantian moda, transportasi kota